Accident prevention on board ship at sea and in port (Geneva, 1996)
This code of practice aims at improving safety at sea by providing guidelines to evaluate the special risks of bulk cargoes such as oil, gas and chemicals, and the hazards relating to rollon/rolloff vessels, ferries and container ships. It also deals with generic problems - anchoring, mooring, access to the ship, use of hoisting devices, general cargo working and maintenance, for example - taking account of the changing nature of seaborne commerce in recent years.